Trust, perceived ease of use, perceived usefulness, and attitude on behavioral intention to use mobile payment - Nova Meta Saputri; Rahmiati (Operations Management and Information System Studies, 2023)
This study aims to test and analyze: (1) The effect of trust on attitude toward using mobile payments in Padang City. (2) The effect of perceived ease of use on attitude toward using mobile payments in Padang City. (3) The influence of perceived usefulness on attitude toward using mobile payments in Padang City. (4) The effect of perceived ease of use on perceived usefulness in Padang City. (5) The effect of trust on behavioral intention to use mobile payments in Padang City. (6) The effect of perceived usefulness on behavioral intention to use mobile payments in Padang City. (7) The effect of attitude toward using on behavioral intention to use mobile payments in Padang City. The population in this study are users of the mobile payment service in Padang City in 2023. The sample size in this study was 202 respondents. Data was collected by distributing questionnaires online and data analysis was carried out using the Smart PLS software. The results of this study indicate that all of the hypotheses are supported.